2021
DOI: 10.1038/s41378-020-00235-w
|View full text |Cite
|
Sign up to set email alerts
|

Self-powered ammonia synthesis under ambient conditions via N2 discharge driven by Tesla turbine triboelectric nanogenerators

Abstract: Ammonia synthesis using low-power consumption and eco-friendly methods has attracted increasing attention. Here, based on the Tesla turbine triboelectric nanogenerator (TENG), we designed a simple and effective self-powered ammonia synthesis system by N2 discharge. Under the driving of the simulated waste gas, the Tesla turbine TENG showed high rotation speed and high output. In addition, the performance of two Tesla turbine TENGs with different gas path connections was systematically investigated and discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…However, during the investigation, we found several limitations restricting the development of the TENG-based nitrogen fixation system. First, the confined application range keeps most of the studies at the experimental level; although some researchers have tried to integrate experimental results with theoretical assumptions 96 to further optimize their works, the conversion efficiency cannot be fully verified. The second issue is the unpredictability of mechanical energy sources, which makes it more imperative and indispensable to enhance the energy harvesting efficiency of TENG devices.…”
Section: Perspectivementioning
confidence: 99%
“…However, during the investigation, we found several limitations restricting the development of the TENG-based nitrogen fixation system. First, the confined application range keeps most of the studies at the experimental level; although some researchers have tried to integrate experimental results with theoretical assumptions 96 to further optimize their works, the conversion efficiency cannot be fully verified. The second issue is the unpredictability of mechanical energy sources, which makes it more imperative and indispensable to enhance the energy harvesting efficiency of TENG devices.…”
Section: Perspectivementioning
confidence: 99%
“…Considering this structure as a parallel-plate capacitor with flat and rigid electrodes for simplification, the electrostatic force exerted on the diaphragm under an AC driving voltage and a DC bias is given by [ 39 ]: where is the electric permittivity of air and is the area of the diaphragm. Advanced models considering the bending of the plate and pull-in limitations are presented in [ 40 , 41 ].…”
Section: Theory and Modeling Of Mems Speakersmentioning
confidence: 99%
“…In 2012, Wang et al , invented a triboelectric nanogenerator (TENG), which can harvest and convert random energy (such as wind energy, wave energy, and raindrop energy) into electricity. The emergence of this TENG technology is a revolutionary breakthrough in energy conversion. TENGs are widely used because of their inherent advantages of low weight, low cost, easy large-scale fabrication, and high conversion efficiency. , TENGs can be directly employed for LEDs, batteries, or intelligent electronics. Compared with conventional electromagnetic generators, TENGs are more efficient at low frequencies (<5 Hz), and their intrinsic characteristics of low current and high voltage make TENGs a type of power source. , Currently, some researchers have designed the structure of TENGs to give them a greater advantage in their application. Zhao et al reported an efficient method for harvesting high-altitude wind energy.…”
mentioning
confidence: 99%
“…26−28 Compared with conventional electromagnetic generators, TENGs are more efficient at low frequencies (<5 Hz), and their intrinsic characteristics of low current and high voltage make TENGs a type of power source. 29,30 Currently, some researchers have designed the structure of TENGs to give them a greater advantage in their application. Zhao et al 31 reported an efficient method for harvesting high-altitude wind energy.…”
mentioning
confidence: 99%